Qualitative Exploration of a Smoking Cessation Trial for People Living With HIV in South Africa. Issue 9 (16th June 2017) - Krishnan, Nandita; Gittelsohn, Joel; Ross, Alexandra; Elf, Jessica; Chon, Sandy; Niaura, Raymond; Martinson, Neil; Golub, Jonathan E
Abstract: Introduction: In South Africa, people living with HIV have a high prevalence of smoking, which undermines the beneficial effects of antiretroviral therapy. However, little is known about barriers to smoking cessation and what interventions work for people living with HIV in this setting. Methods: A randomized trial comparing intensive anti-smoking counseling versus counseling and nicotine replacement therapy was recently concluded in Klerksdorp, South Africa. In a post-trial follow-up, 23 in-depth interviews with patients and one focus group discussion with counselors from the trial were conducted. A codebook was developed and codes were applied to the transcripts, which were analyzed using a thematic analysis. Results: Barriers at the economic, social/interpersonal, and individual levels induced stress, which hindered smoking cessation. Economic stressors included unemployment and poverty. Social or interpersonal stressors were lack of social support for quitting smoking and lack of social support due to having HIV. Individual stressors were traumatic life events. Alcohol was used to cope with stress and frequently co-occurred with smoking. Managing cravings was a barrier unrelated to stress. Participants proposed income and employment opportunities, group counseling, and more frequent counseling as solutions to address stressors at different levels. Nicotine replacement therapy was helpful to mitigate cravings. Conclusions: Future smoking cessation interventions need to target barriers at multiple levels. Increasing the supply and duration of nicotine replacement therapy may increase its effectiveness. Other behavioral approaches such as group counseling or peer counseling could hold promise in this setting but need to be tested for efficacy through randomized controlled trials. Implications: To our knowledge, this is the first qualitative study examining barriers to smoking cessation for people living with HIV in South Africa. Smoking is highly prevalent among people with HIV in South Africa and cessation interventions are urgently needed. A better understanding of barriers to smoking cessation that people with HIV face will lead to the development of contextually appropriate interventions. This study also provides feedback on interventions from a recently concluded smoking cessation randomized trial and will help guide the design of future smoking cessation trials.